2007
DOI: 10.1007/s11554-007-0045-x
|View full text |Cite
|
Sign up to set email alerts
|

A new fast reversible method for image safe transfer

Abstract: In this paper a novel reversible method for fast and safe image transfer is proposed. The method combines compression, data hiding and partial encryption of images in a single processing step. The proposed approach can embed data into the image according to the message size and partially encrypt the image and the message without changing the original image content. Moreover, during the same process the image is lossless compressed. Nevertheless, the compression rate depends on the upper bound of message size t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Real-time The experiments have shown that we can achieve the desired level of encryption in each frame, while maintaining the full AVS video coding standard compliance, under a minimal set of computational requirements. The proposed system can be extended to protect only ROI [17] in video surveillance and can be applied to medical image transmission [18].…”
Section: Resultsmentioning
confidence: 99%
“…Real-time The experiments have shown that we can achieve the desired level of encryption in each frame, while maintaining the full AVS video coding standard compliance, under a minimal set of computational requirements. The proposed system can be extended to protect only ROI [17] in video surveillance and can be applied to medical image transmission [18].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is perfect for multimedia playback on handheld devices. The proposed system can be extended for ROI specific video protection [11] for video surveillance and can be applied to medical image transmission [10]. …”
Section: Resultsmentioning
confidence: 99%
“…TRANSFER [4] In this section a novel reversible method for fast and safe image transfer is proposed. The method combines compression, data hiding and partial encryption of images in a single processing step.…”
Section: A New Fast Reversible Methods For Image Safementioning
confidence: 99%
“…Our approach reduces then the computational effort and the required computation time. This method is specially suited for medical images where one can associate the patient diagnostic to the concerned medical image for safe transfer purpose [4]. The keywords of this work are fast and safe image transmission, lossless compression, reversible data hiding, partial encryption, image protection and real time image processing.…”
Section: A New Fast Reversible Methods For Image Safementioning
confidence: 99%